Purr Paws / Nurul Izzati Mohammad Shukor - Mohammad Shukor, Nurul Izzati (2021)
Given name for this business is Purr Paws. Purr is the short form from colour of purple since I like purple and paws stand for love towards cats. This business based in Jalan SS13/1G Subang Jaya and it was established in February 2021. Purr Paws was established as the love of owner towards skincare products. As an acne survivor for 4 years, I believe people with acne problems can recover one day and that does not mean they are not pretty. We have to embrace our flaws and one day we will own clear skin and glow like others. With trademark of “Grow and Glow”, let us grow and glow together to achieve healthy and glowing skin. Mission of this business is to provide customer with affordable price of every international product and guaranteed authenticity. While vision is to be the first choice of skincare shop to all skincare junkies. To achieve our organization’s goals, we always find for good bargain of skincare products, and we sell it with an affordable price. Those products that we sell are not available on Malaysia as it were mostly from United Kingdom and United States. Sometimes, my agent would search for discounted products, so customer do not have to pay for the normal price. From many choices of brand to choice from, customer could buy with reasonable price. This business is based as a dropship under the owner, Syaza Syazwana binti Mat Zabidi and the agent, Nur Atika binti Zulkifli. I am as the authorized dropship has the responsibility to promote for all available products in the shop. As attached below, will be the price list of all products in the shop. From this report also will include the prove from creating facebook page, customing URL page, and seven postings of teasers. Apart from teasers, there will also be every results from hard sell copywriting, soft sell copywriting, frequency of posting. All postings from each categories have included with some graphics to attract attention of Facebook users.